Drying stability enhancement of red-perovskite colloidal ink via ligand-derived coating for inkjet printing. Issue 5 (1st March 2021) - Yoo, Jung Hyeon; Jeong, Seong Guk; Choi, Seung Hee; Kwon, Seok Bin; Song, Young Hyun; Yoon, Dae Ho
Abstract: Today, inkjet printing techniques has many merits such as high printing yield and mask-free process for the various field. As one of the candidate ink materials, the perovskite is appropriate for inkjet printing due to the colloidal state and excellent optoelectronic properties such as high photoluminescence quantum yield (PLQY) and narrow full width at half maximum (FWHM). Those characteristics are an advantage to fabricating ink and realize wide color-gamut in the small area with micro-patterning. However, perovskite application in inkjet printing with various color has limitations due to the low drying stability of mixed halide perovskite. Herein, we report on improving the drying stability of red perovskite by inducing aggregation during the drying process. Silane ligand has applied to induce the aggregation, and we confirmed that the thin coating layer has formed on the perovskite surface. The synthesized red-perovskite using silane ligands is well dispersed in the solvent as a colloidal state. And it maintained the emission intensity over 50% after drying. As-prepared perovskite ink has successfully printed on the ethyl cellulose film with 338 dpi with maintaining transparency of the film. These results are beneficial not only display applications but also security applications such as double anti-counterfeiting.